2013
DOI: 10.1002/mnfr.201300368
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 PUFA supplementation and the response to evoked endotoxemia in healthy volunteers

Abstract: Scope Fish oil-derived n-3 PUFA may improve cardiometabolic health through modulation of innate immunity; however, findings in clinical studies are conflicting. We hypothesized that n-3 PUFA supplementation would dose-dependently reduce the systemic inflammatory response to experimental endotoxemia in healthy humans. Methods and Results The Fenofibrate and omega-3 Fatty Acid Modulation of Endotoxemia (FFAME) study was an 8-week randomized double-blind trial of placebo or n-3 PUFA supplementation (Lovaza 465m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…The RBCs were added to an internal standard (dried using nitrogen gas) containing labeled fatty acids (d 8 at Ϫ 80°C until extraction. For the study Evoked Endotoxemia , RBCs were obtained from venous blood as described in ( 38 ).…”
Section: Human Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The RBCs were added to an internal standard (dried using nitrogen gas) containing labeled fatty acids (d 8 at Ϫ 80°C until extraction. For the study Evoked Endotoxemia , RBCs were obtained from venous blood as described in ( 38 ).…”
Section: Human Studiesmentioning
confidence: 99%
“…Details on the analysis of the panel of infl ammatory responses to the administration of LPS, consisting of TNF-␣ , interleukin (IL)-6, IL-10, IL-1-receptor antagonist (RA), monocyte chemoattractant protein-1 (MCP-1), C-reactive protein (CRP), and serum amyloid A (SAA), have been published in ( 38 ).…”
Section: Markers Of Infl Ammatory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…However, an endotoxemia model applying such relatively high LPS doses is not preferred as methodological tool in clinical pharmacology studies since the elicited immune response is so strong that potential effects of immune-modulating interventions may not be observed, other homeostatic mechanisms may be temporarily impaired, and, importantly, the elicited immune response at these LPS doses is not free of risk for the volunteer. Studies applying lower LPS doses have been performed [9,10], but thorough characterization of a human endotoxemia model at lower LPS dose levels is desired. In the current study, 0.5 ng/kg was selected as the lowest LPS dose to be administered intravenously because an LPS dose of 0.2 ng/kg was shown previously to elicit no cytokine response in vivo [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, even if most of randomized trials with LC n-3 PUFAs have reported consistent decreased inflammation in groups with high baseline inflammation (stressed students, elderly, diabetics, and hypertriglyceridemic subjects), results are mixed (Fritsche, 2006). Indeed, DHA/EPA dietary supplementation in healthy subjects blunted the endocrine stress response and the increase in body temperature, with or without impact on cytokine production after bacterial endotoxin administration (Ferguson et al, 2014;Michaeli et al, 2007). AD patients supplemented with a DHA-rich diet display reduced release of proinflammatory cytokines (IL-1β, IL-6, GM-CSF) from stimulated peripheral blood mononuclear cells (Vedin et al, 2008).…”
Section: N-pufas Neuroinflammation and Cognitive Disordersmentioning
confidence: 99%